Hybrid Polyester-Hydrogel Electrospun Scaffolds for Tissue Engineering Applications - Gonçalves de Pinho, Ana Rita; Odila, Ines; Leferink, Anne; van Blitterswijk, Clemens; Camarero-Espinosa, Sandra; Moroni, Lorenzo (Frontiers in Bioengineering and Biotechnology, 2019)
Electrospinning is an attractive fabrication process providing a cost-effective and straightforward technic to make extra-cellular matrix (ECM) mimicking scaffolds that can be used to replace or repair injured tissues and organs. Synthetic polymers as poly (ε-caprolactone) (PCL) and poly (ethylene oxide terephthalate)-poly(butylene terephthalate) (PEOT/PBT) have been often used to produce scaffolds due to their good processability, mechanical properties, and suitable biocompatibility. While synthetic polymers can mimic the physical features of native ECM, natural polymers like alginate are better suited to recapitulate its hydrated state or introduce functional groups that are recognized by cells (e.g. –NH2). Thus, this study aims at creating electrospun meshes made of blended synthetic and natural polymers for tissue engineering applications. Polyethylene oxide (PEO), PCL and PEOT/PBT were used as a carrier of Alginate. Scaffolds were electrospun at different flow rates and distances between spinneret and collector (air gap), and the resulting meshes were characterised in terms of fibre morphology, diameter, and mesh inter-fibre pore size. The fibre diameter increased with increasing the flow rate, while there was no substantial influence of the air gap. On the other hand, the mesh pore size increased with increasing air gap, while the effect of flow rate was not significant. Cross-linking and washing of alginate electrospun scaffolds resulted in smaller fibre diameter. These newly developed scaffolds may find useful applications for tissue engineering strategies as they resemble physical and chemical properties of tissue extra-cellular matrix. Human Dermal Fibroblasts were cultured on PCL and PCL/Alginate scaffolds in order to create a dermal substitute.